Middle English Origins of Present-Day Distinction in the Pronunciation of Word-Final or Pre-Consonantal Sequences -or, -oar, -oor, -our - Fernández Guerra, Ana (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen